Tailoring Multiferroic Characteristics in LaFeO3 Nanocrystals via Rare-Earth Pr3+ Doping - Ramesh Kumar Raji; Tholkappiyan Ramachandran; Fathalla Hamed; Srinivasa S (Advances in Condensed Matter Physics)
Multiferroic materials have sparked significant interest in the realm of materials science because of their potential impact on various device applications. This study focuses on the synthesis of nanocrystalline La1−xPrxFeO3 (LPFO) materials, where x can be either 0 or 0.5, using a solid-state technique. The aim is to gain insights into their structural, optical, dielectric, and magnetic properties. To confirm the chemical phase of the synthesized materials, X-ray diffractometer and Raman spectroscopy were employed. The outcome of the Rietveld analysis reveals that the LPFO crystallites exhibit orthorhombic symmetry with a Pbnm space group. The functional groups that were present in the LPFO samples were identified using FT-IR spectroscopic analysis. The morphological studies using scanning electron microscope and transmission electron microscope indicate that the synthesized samples exhibit excellent homogeneity with uniformly distributed grains. In order to investigate the dielectric constant (εʹ) and dielectric loss (tan δ) were examined as functions of temperature and frequency. Pr3+ dopants had a notable impact on the dielectric characteristics, particularly within the frequency span of 10 kHz–1 MHz and over the temperature variation of 40–160°C. The ambient temperature magnetic properties of the LPFO ferrite materials displayed antiferromagnetic behavior. Ultimately, this research reveals insightful information on the structural, optical, dielectric, and magnetic properties of the synthesized nanocrystalline LPFO materials, shedding light on their potential applications in the multifunctional devices.